Energy performance, environmental impact and cost of a range of insulation materials. (April 2021) - Dickson, T.; Pavía, S.
Abstract: The need for the selection of an appropriate insulation is becoming more important as environmental problems continue to grow. This paper investigates insulation performance in terms of heating energy requirement, environmental impact and cost. The thermal performance of insulations (natural, petrochemical, rock/slag based) is modelled, on brick, rammed earth (RE) and cavity walls, in different locations (external, internal and inside the wall), using software. The environmental performance of the insulation is determined using the Life Cycle Assessment-LCA-technique. A new scoring tool is created which allows inputted data, across the three areas of performance (energy, environmental, economic), to be standardized and compared, providing a final score that represents the overall performance. The input data and weightings can be modified easily to investigate new materials and to meet user requirements. Out of all the insulations, cellulose fibre showed the best overall performance. The model results highlight the importance of the hygrothermal properties of the insulation, and their compatibility with the substrate, for best energy performance. The insulated earth buildings require less energy for heating and are responsible for lower carbon emissions than the insulated brick buildings. This is attributed to the lower diffusivity of the earth walls attenuating external temperature fluctuation and economizing energy. The permeable insulations (cork and hemp) tend to perform better with earth than with brick, which is attributed to a more compatible hydric performance. The model results indicate that the best thermal performance is obtained when insulation is placed outside the wall. Highlights: A flexible tool that allows to compare the energy performance (modelled with software), environmental impact (assessed with LCA) and economy of an insulation is produced. The energy performance is based on thermo-hygric properties, heat transfer, room heat gains, air exchanges and weather data, and the insulations are modelled (externally/internally) on brick, cavity and earth walls. Cellulose fibre was the best performer, and the permeable insulations (cork and hemp) perform better with earth, highlighting the importance of the insulation's hygrothermal properties. The insulated earth buildings (with lower diffusivity) require less energy for heating and produce lower carbon emissions. According to the models, thermal performance is best when the insulation is placed outside the wall.